Safety and Feasibility of Rotational Atherectomy for Retrograde Recanalization of Chronically Occluded Coronary Arteries - Wang, Jing; Huang, Junlin; Yakubu, Abdul-Subulr; Wu, Kaize; Huang, Zehan; Zhong, Zhian; Liao, Hongtao; Zhang, Bin (Frontiers in Cardiovascular Medicine, 2022)
Objective To evaluate the safety and feasibility of rotational atherectomy (RA) in retrograde chronic total occlusion percutaneous coronary intervention (CTO-PCI) by analyzing immediate and long-term outcomes. Background Recent evidence supports the safety and feasibility of RA in CTO-PCI. However, few studies have focused on the use of RA in a retrograde approach to percutaneous revascularization of chronic total occlusion (CTO) lesions and information on long-term outcomes is lacking. Methods A total of 329 patients who underwent retrograde CTO-PCI, out of 1496 consecutive CTO-PCI patients from April 2017 to July 2020, were retrospectively recruited from the 2nd Cardiology Department of the Guangdong Provincial People's Hospital. 16 patients underwent RA (RA group) whilst 313 did not (non-RA group). Results Technical (87.5% vs. 87.5) and procedural (85.9% vs. 87.5) success rates were similar between both groups. There was no difference concerning major procedural complications between groups (12.5% vs. 19.2%; p > 0.75). No in-hospital MACCEs was recorded in the RA group while there were eight MACCEs in the non-RA group (p > 0.99). In the RA group, 2 cases recorded perforation (1 target vessel perforation case and 1 branch vessel perforation), and 55 cases of vessel perforations/dissections were recorded in non-RA group including 18 target vessel perforations, 2 branch vessel perforations, 35 collateral vessel perforations (one patient died from cardiac tamponade). No difference was found in terms of the perforation rate between the two groups (p > 0.99). Over a mean follow-up period of 26.47 ± 14.46 months, use of RA in retrograde CTO-PCI did not result in an increased mortality rate [hazard ratio (HR) 1.58, 95% confidence interval (CI), 0.31–8.21, p = 0.65], major adverse cardiac and cerebral events (HR 0.99, 95% CI 0.35–2.79, p = 0.99) or overall rehospitalization rate (HR 1.27, 95% CI 0.44–3.67, p = 0.67). Adjusted Kaplan–Meier curves according to Cox regression model suggested several predictors influencing the all-cause mortality, cardiovascular mortality, MACCEs, stroke rate, non-fatal myocardial infarction, target vessel recanalization rate and rehospitalization rate in the comparison. Conclusions Our study demonstrates that the in-hospital outcomes and long-term follow up events were the same between RA and non-RA retrograde CTO-PCI patients. RA offered an option for skillful operators in difficult cases when the lesion was severely calcified in retrograde CTO-PCI.